Fabrication and application of composite adsorbents made by one-pot electrochemical exfoliation of graphite in surfactant ionic liquid/nanocellulose mixtures - Azmi Mohamed (Tanjung Malim, 2021)
Fabrication and application of composite adsorbents made by one-pot electrochemical exfoliation of graphite in surfactant ionic liquid/nanocellulose mixtures by Azmi Mohamed